Perlindungan Hukum Terpidana terhadap Putusan Hakim Berdasar Alat Bukti yang Lemah menurut Sistem Hukum di Indonesia (SETARA : Jurnal Ilmu Hukum, 2019)
This study examines legal protection for convicted persons who are sentenced on the basis of weak evidence under Indonesian criminal procedure law. Using normative juridical research with statutory and case approaches, the article reviews the 1945 Constitution, Law Number 8 of 1981 on Criminal Procedure, Government Regulation Number 92 of 2015, and several well-known wrongful-conviction or evidentiary controversy cases, including Sengkon-Karta, Risman Lakoro, Jessica Kumala Wongso, and Pollycarpus. The study finds that legal protection for convicted persons is still limited, even though the principle of human dignity requires stronger safeguards against judicial error. Existing regulation, especially Article 95 of the Criminal Procedure Code, has not yet provided adequate protection for convicted persons who later prove not to be the actual perpetrators. The article therefore argues that Indonesian criminal procedure law needs stronger remedial norms and a more balanced evidentiary approach in order to protect both public order and the rights of individuals facing conviction.
Keywords: Legal Protection; Convicted Person; Weak Evidence; Criminal Procedure; Wrongful Conviction